Upaya Menjaga Kemurnian dan Validitas Hadis Nabi: Kajian terhadap Sejarah Kodifikasi Hadis - Bahrah, Mush'ab; Y., Muhammad Ansori (TAJDID, 2022)
Hadith as the main foundation of Islamic law, second after the Holy Qur'an, has a very large role and portion in the history of Islam. Since the revelation of Islam in the period of the Prophet Muhammad until periods after that: the companions, tabi'in, tabi'ut tabi'in, also the scholars after to the present day. If the Qur'an is a direct revelation from Allah, the hadith is its complement and explanation that comes directly from the Prophet Muhammad, which of course also remains under the direct supervision of Allah. This paper is made so that Muslims can understand correctly the nature of the hadith itself, how its role and development has been until now, which explains that hadith are words, actions, decisions, and moral characteristics that come from the Prophet Muhammad. Because these hadiths are very numerous, the companions and tabiin have tried their best to maintain the purity and validity of these hadiths. So then came the Ilm Hadith Riwayah and Ilm Hadith Dirayah compiled by Muslim scholars to be taught to generations so that Muslims can continue to maintain existing hadiths, can understand them correctly and can distinguish between hadiths that are truly authentic and hadiths that are not. In addition, since the period of the companions and tabi'in the scholars also have started the codification (official book-making) of hadiths. The purpose is the same which is to maintain the purity of the traditions of the Prophet Muhammad so that they can continue to be maintained and conveyed to the future generations.